A shared structural solution for neutralizing ebolaviruses - Ollmann Saphire, Erica (Henry Stewart Talks, 2011)
Structure of Zaire ebolavirus GP Receptor binding, Cathepsin cleavage, Immune evasion Structure of Sudan ebolavirus GP, GP epitopes of two neutralizing antibodies, Proposed conformational changes in fusion